Study of hepatotoxicity and oxidative stress in male Swiss-Webster mice exposed to functionalized multi-walled carbon nanotubes - Patlolla, Anita K. (2011)
Carbon nanotubes (CNTs), the most promising material with unique characteristics, find its application in different fields ranging from composite materials to medicine and from electronics to energy storage. However, little is known about the mechanisms behind the interaction of these particles with cells and their toxicity. The aim of this study was to assess the effects, after intraperitoneal injection, of functionalized multi walled carbon nanotubes (MWCNT) (carboxyl groups) on various hepatotoxicity and oxidative stress biomarkers (ROS, LHP, ALT, AST, ALP and morphology of liver) in the mouse model. The mice were dosed intraperitoneally at 0.25, 0.5 & 0.75 mg/kg/day for 5 days of purified/functionalized MWCNTs and two controls (negative; saline and positive; carbon black 0.75 mg/kg) as appropriate. Samples were collected 24 hours after the fifth day treatment following standard protocols. Exposure to carboxylated functionalized MWCNT; the body-weight gain of the mice decreased, induced reactive oxygen species (ROS), and enhanced the activities of serum amino-transferases (ALT/AST), alkaline phosphatases (ALP) and concentration of lipid hydro peroxide compared to control. Histopathology of exposed liver showed a statistically significant effect in the morphological alterations of the tissue compared to controls. The cellular findings reported here do suggest that purified carboxylated functionalized MWCNT has the potential to induce hepatotoxicity in Swiss-Webster mice through activation of the mechanisms of oxidative stress, which warrant in vivo animal exposure studies. However, more studies of functionalization in the in vivo toxicity of MWCNTs are required and parallel comparison is preferred.